The Relationship Between Computed Tomography Density Values and Platelet Number and Function in Acute Intracerebral Hematomas - Unlu, Ebru; Ulu, Sena; Ozdinc, Serife; Dogan Baki, Elif; Kacar, Emre; Beker Acay, Mehtap; Karavelioglu, Ergun; Yilmaz, Emel; Uzel Tas, Hanife (Annals of Medical Research, 2021)
None